IMPROVING STUDENTS VOCABULARY MASTERY THROUGH ENGLISH FUN LEARNING WITH BLOOKET GAMES AT SMP SANTO ANTONIUS, JAKARTA TIMUR - Rr. Isyamirahim; Yanti Rusmiati; Ika Chairiyani (JPGENUS: Jurnal Pendidikan Generasi Nusantara, 2024)
This research aims to improve the vocabulary mastery of seventh grade students at Santo Antonius Middle School, East Jakarta, through fun English learning using the Blooket game. The method used was Classroom Action Research (CAR) involving 22 students as samples. This research was carried out in two cycles, where each cycle consisted of four stages: planning, action, observation, and reflection. Data collection was carried out through qualitative and quantitative techniques. Qualitative data was obtained from interviews with students before and after the cycle, as well as observations during class activities. Quantitative data was obtained from tests before and after the action. The results showed that the use of the Blooket game significantly increased students' vocabulary mastery. Based on these findings, it is concluded that learning vocabulary through interactive games such as Blooket can create a fun and effective learning atmosphere.